Estimation of the loss of coastal land, due to the anticipated sea-level rise, in the case of the coastal zone from Chalkoutsi to Nea Palatia (S. Evoikos gulf) - Πούλος, Σ.; Πετράκης, Σ.; Καλύβα, Δ.; Πουχαρίδου, Μ. (Bulletin of the Geological Society of Greece, 2011)
In the present study, the effect of the anticipated sea-level rise is investigated along the coastal zone extending in between Chalkoutsi and Nea Palatia that is located in southern coast of the semi-enclosed Southern Evoikos Gulf. The terrestrial part of the coastal zone consists of low-lying alluvial deposits, including the sensitive coastal environments of the delta of Asopos river and the Oropos lagoon located ~3 km to the east of the R. Asopos mouth. The area under investigation is already under erosion (locally, coastline retreat accounts for several metes) despite the fact that it is exposed to moderate wave conditions (average wave heights <1 m, with maximum values <2.7 m). The calcu-lated loss of coastal land, due to the anticipated sea-level rise of 0.38 m and 1 m, accounts 4-4.5 km2 and 21-23.5 km2, respectively.